Vulnerability Mapping To Pollution of Shallow Aquifers of the Bani Transboundary Catchment (Cote D?ivoire, Mali) Using The Drastic Method - Jean, Kouamé Kan; Patrice, Jourda Jean; Hubert, Signo Kouassi; Bachir, Saley Mahaman; Tawa, Anani Abenan; Kouakou, Deh Serge; Adama, Mariko; Jean, Biémi (Journal of Asian Scientific Research, 2013)
This study was conducted in the RIPIECSA (Interdisciplinary and Participatory Research on the Interactions between Ecosystems, Climate and Societies of West Africa) project led by Mali on climate variability, agricultural intensification and its impact on water resources of Bani River. The activities which could damage the water quality have been made on the Bani River. Overall purpose of this study is to determine the degree of protection against pollution of shallow aquifers in the watershed borders of Bani River (Côte d'Ivoire, Mali), to ensure their sustainable exploitation. This knowledge requires the development of vulnerability map to aquifers pollution. The vulnerability map has been developed using DRASTIC method by exploiting the capabilities offered by GIS software ArcGIS 9.3.The analysis of this vulnerability map highlights four classes of vulnerabilities from "very low" vulnerability degree to "high" vulnerability. The class of "medium vulnerability" is the most dominant, expressed with 65.78% of the mapped areas. It covers an area of 62528 km². On the scale of hydrogeological vulnerability, this class belongs to category 2 which corresponds to an uncertain hydrogeological protection. The very high vulnerability class doesn’t exist into the basin. Areas targeted with high sensitivity may be protected by prohibiting certain activities in these areas.